2013
DOI: 10.1002/j.1552-4833.2013.35942.x
|View full text |Cite
|
Sign up to set email alerts
|

Practices and Policies of Clinical Exome Sequencing Providers: Analysis and Implications

Abstract: Exome and whole genome sequencing (ES/WGS) offer potential advantages over traditional approaches to diagnostic genetic testing. Consequently, use of ES/WGS in clinical settings is rapidly becoming commonplace. Yet there are myriad moral, ethical, and perhaps legal implications attached to the use of ES and health care professionals and institutions will need to consider these implications in the context of the varied practices and policies of ES service providers. We developed "core elements" of content and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(33 citation statements)
references
References 20 publications
0
32
1
Order By: Relevance
“…A recent comparison of written consent forms for genetic testing also showed variability in the type of information disclosed, with several laboratories using the same consent form for single and panel-based testing [54,55]. Despite concerns about incidental findings and its prominence with the use of genomic tests (whole genome or exome testing [54][55][56]; chromosomal microarrays arrays [57]), this potential was only disclosed by three laboratories. Perhaps due to the use of more targeted testing platforms (i.e., genotyping for common variants), the issue of incidental findings is of less concern for PGx testing.…”
Section: Discussionmentioning
confidence: 99%
“…A recent comparison of written consent forms for genetic testing also showed variability in the type of information disclosed, with several laboratories using the same consent form for single and panel-based testing [54,55]. Despite concerns about incidental findings and its prominence with the use of genomic tests (whole genome or exome testing [54][55][56]; chromosomal microarrays arrays [57]), this potential was only disclosed by three laboratories. Perhaps due to the use of more targeted testing platforms (i.e., genotyping for common variants), the issue of incidental findings is of less concern for PGx testing.…”
Section: Discussionmentioning
confidence: 99%
“…As neither approach is simple or inexpensive to implement, many laboratories eschew such confirmatory testing during routine analysis. While PCR-based dideoxy sequencing ("Sanger" sequencing) is a generally accepted method of confirmatory testing for constitutional clinical NGS [17][18][19][20] , its sensitivity is limited to approximately 10%-20% VAF. As cancer NGS testing routinely identifies clinically relevant mutations from 5%-10% VAF, it Sanger is not an ideal method for confirmation for all variants.…”
Section: Technical Validitymentioning
confidence: 99%
“…In contrast to whole-genome sequencing (WGS), whole-exome sequencing (WES) focuses on the ~2 % of the genome that is protein coding, thus reducing cost and easing interpretation (Bick and Dimmock 2011). The successful use of WES in the research setting to identify causal mutations in challenging medical conditions was quickly translated into its rapid incorporation in molecular diagnostics (clinical exome sequencing or CES) (Jamal et al 2013). The first large-scale study to assess the diagnostic yield of CES was in 2013 and reported a yield of ~25 %, mostly in patients with neurodevelopmental disorders (Yang et al 2013).…”
Section: Introductionmentioning
confidence: 99%